1985
DOI: 10.1021/bi00330a015
|View full text |Cite
|
Sign up to set email alerts
|

Arrangement of the subunits of the nicotinic acetylcholine receptor of Torpedo californica as determined by .alpha.-neurotoxin crosslinking

Abstract: [3H]Methyl-alpha-neurotoxin prereacted with dithiobis(succinimidyl propionate) (DTSP) can be covalently linked to each of the subunits of the nicotinic acetylcholine receptor in membranes from the electric tissue of Torpedo californica. Pronounced changes in the cross-linking pattern are observed upon prior incubation with receptor specific ligands and upon reduction and/or alkylation of the receptor. d-Tubocurarine has been shown to bind to two different sites in receptor-rich membranes. These sites are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
2

Year Published

1986
1986
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 37 publications
0
22
0
2
Order By: Relevance
“…a-Btx has been shown to bind to the a subunits (22,23), and since the binding of a-Btx and a-Ntx is mutually exclusive and they both inhibit photoaffinity labeling of the a-subunit (24,25), it is believed that also a-Ntx binds to the high-affinity binding sites for cholinergic ligands present on the a subunits. Results, obtained with a-Ntx cross-linked to the AcChoR subunits and with an electron microscopic approach using a-Ntx complexed to biotin-avidin, support the notion that also a-Ntx binds to the a subunits (26,27). a-Ntx and a-Btx bind to the AcChoR molecule with a stoichiometry of 2:1 (reviewed in ref.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…a-Btx has been shown to bind to the a subunits (22,23), and since the binding of a-Btx and a-Ntx is mutually exclusive and they both inhibit photoaffinity labeling of the a-subunit (24,25), it is believed that also a-Ntx binds to the high-affinity binding sites for cholinergic ligands present on the a subunits. Results, obtained with a-Ntx cross-linked to the AcChoR subunits and with an electron microscopic approach using a-Ntx complexed to biotin-avidin, support the notion that also a-Ntx binds to the a subunits (26,27). a-Ntx and a-Btx bind to the AcChoR molecule with a stoichiometry of 2:1 (reviewed in ref.…”
mentioning
confidence: 56%
“…a-Dtx is a cholinergic antagonist closely related to a-Ntx and a-Btx because it belongs to the same protein family and is highly homologous to them (21,39). These toxins are powerful blockers of muscle and electric organ AcChoR by virtue of their ability to bind to the two a subunits (22,23,26,27) in a competitive fashion with acetylcholine, carbamoylcholine, curare, and other classic cholinergic ligands (21,52). a-Btx binds to a segment of the a subunit very close to or overlapping with the segment containing a cysteine residue labeled by cholinergic labels (53).…”
Section: Effect Of A-dtx On the Dissociation Rate Of A -Btx-acchormentioning
confidence: 99%
“…However, it was noted (8) that p-(dimethylamino)benzenediazonium fluoroborate was specifically photoincorporated into the y subunit at a level 10%1 of a subunit. In addition, chemical crosslinking of 3H-labeled cobra toxin to the AcChoR resulted in reaction with all subunits that could be blocked selectively by TC (19). UV-induced crosslinking of '25I-labeled a-BTX to the AcChoR resulted in covalent attachment to the a, y, and 8 subunits (20).…”
Section: The Specificity Of [3h]tc Photoincorporation Into Thementioning
confidence: 99%
“…Several lines of evidence indicate that neighboring subunits affect ligand binding. a-BTX binds to isolated a subunit and not the other subunits (10,(16)(17)(18), while covalent incorporation of a-BTX by chemical (19) or photochemical (20) crosslinking indicates proximity of other subunits to the a-BTX binding site. Recent studies from the coexpression of pairs of subunits in quail fibroblasts indicate that coexpression of a and y subunits is required for highaffinity binding of TC, whereas low-affinity binding requires the coexpression ofa and 8 subunits (21).…”
mentioning
confidence: 99%
“…Points of attachment of ␣-neurotoxin within the nAChR binding sites have been examined by cross-linking chemically modified (8,9) or photoactivatable derivatives of ␣-neurotoxin (10 -13) and by simple ultraviolet irradiation without chemical modification (14). These labeling studies have suggested contacts with both ␣ and non-␣ subunits at the binding sites (see Refs.…”
mentioning
confidence: 99%